2022
DOI: 10.1002/1873-3468.14519
|View full text |Cite
|
Sign up to set email alerts
|

Radical SAM enzymes: Nature's choice for radical reactions

Abstract: Enzymes that use a [4Fe‐4S]1+ cluster plus S‐adenosyl‐l‐methionine (SAM) to initiate radical reactions (radical SAM) form the largest enzyme superfamily, with over half a million members across the tree of life. This review summarizes recent work revealing the radical SAM reaction pathway, which ultimately liberates the 5′‐deoxyadenosyl (5′‐dAdo•) radical to perform extremely diverse, highly regio‐ and stereo‐specific, transformations. Most surprising was the discovery of an organometallic intermediate Ω exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 82 publications
3
11
0
Order By: Relevance
“…As expected, both 11a and 11b exhibit reduced inhibition of PRMT1 and PRMT3, as one of the parental compounds (7) does not significantly inhibit either of the two PRMTs. 11a has a remarkable reduction (∼116×) in inhibition of PRMT1 from that of 6e (IC 50 of 14 μM vs. 0.12 μM) (Figure 2C).…”
Section: ■ Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…As expected, both 11a and 11b exhibit reduced inhibition of PRMT1 and PRMT3, as one of the parental compounds (7) does not significantly inhibit either of the two PRMTs. 11a has a remarkable reduction (∼116×) in inhibition of PRMT1 from that of 6e (IC 50 of 14 μM vs. 0.12 μM) (Figure 2C).…”
Section: ■ Resultssupporting
confidence: 75%
“…The desired compounds 11a and 11b were synthesized following the reported methods 48 (Scheme 1). Briefly, the commercially available 6chloropurine ribonucleoside reacted with 3-phenylpropylamine to yield N6-phenylpropyladenosine (7), which was then subjected to the Mitsunobu reaction to produce compound 8. Then the acetyl group of 8 was removed, followed by its substitution with Boc protected ethyl or propyl amine.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radical S -adenosyl- l -methionine (SAM) enzymes are ubiquitous in life, comprising one of the largest enzyme superfamilies. These enzymes catalyze the reductive cleavage of SAM by electron transfer from a [4Fe-4S] 1+ cluster to the sulfonium group of the coordinated SAM to form the highly reactive 5′-deoxyadenosyl radical (5′-dAdo•), which then ultimately abstracts a hydrogen atom from substrates. However, rapid freeze-quench electron paramagnetic (EPR) and electron nuclear double-resonance (ENDOR) spectroscopies have shown that prior to H abstraction from the substrate, 5′-dAdo• forms an organometallic intermediate, denoted Ω, that is characterized by a direct bond between the [4Fe-4S] 3+ cluster and 5′C of 5′-dAdo (Figure , left). , Later, it was shown that photo-reductive cleavage of SAM in a broad subset of radical SAM (RS) enzymes releases either 5′-dAdo• or a methyl radical (•CH 3 ); ,, upon annealing, the latter forms an alternative organometallic species, denoted Ω Μ , which was shown by ENDOR to have a [4Fe-4S] 3+ cluster with a Fe–CH 3 bond (Figure , middle). Inspired by these discoveries, the M–CH 3 analogue of Ω Μ (Figure , right) was synthesized and extensively characterized by crystallography as well as with Mossbauer and ENDOR spectroscopic methods, , with additional alkylated iron–sulfur clusters being synthesized and characterized. …”
Section: Introductionmentioning
confidence: 99%
“…Klinman [9] paints a fascinating picture of how function in metalloenzymes can be activated by dynamics and how the interplay between protein dynamics and function can be addressed using novel experimental and theoretical approaches. Broderick and Hoffman review the vast “radical SAM” family of proteins [10]. Enzymes utilizing a 4Fe‐4S cluster together with S ‐adenosyl‐methionine to perform a hugely diverse set of radical‐based chemical reactions.…”
mentioning
confidence: 99%